2013
DOI: 10.1088/0029-5515/53/2/023001
|View full text |Cite
|
Sign up to set email alerts
|

Transport and drift-driven plasma flow components in the Alcator C-Mod boundary plasma

Abstract: Boundary layer flows in the Alcator C-Mod tokamak are systematically examined as magnetic topology (upper versus lower-null) and plasma density are changed. Utilizing a unique set of scanning Langmuir-Mach probes, including one on the high-field side midplane, the poloidal variation of plasma flow components in the parallel, diamagnetic and radial directions are resolved in detail. It is found that the plasma flow pattern can be decomposed into two principal parts: (1) a drift-driven component, which lies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 53 publications
8
68
0
Order By: Relevance
“…Flow along B may appear on the cameras as either toward or away from the X-point depending on whether the pitch of the camera view is greater or less than the pitch of the field. Average parallel flow arises in the edge due to several factors, including Pfirsch-Schlüter effects [18], collisional (neoclassical) flow [39], and sources and sinks [36]. More detailed discussion of the relationship between this theory and the present experimental results is given in Sec.…”
Section: Theoretical Backgroundmentioning
confidence: 80%
See 1 more Smart Citation
“…Flow along B may appear on the cameras as either toward or away from the X-point depending on whether the pitch of the camera view is greater or less than the pitch of the field. Average parallel flow arises in the edge due to several factors, including Pfirsch-Schlüter effects [18], collisional (neoclassical) flow [39], and sources and sinks [36]. More detailed discussion of the relationship between this theory and the present experimental results is given in Sec.…”
Section: Theoretical Backgroundmentioning
confidence: 80%
“…Recent Langmuir probe measurements of turbulent transport in the SOL of CMod have shown that the fluctuation-induced radial particle flux on the high field side midplane location much lower than at the low-field side midplane [18]. Also in C-Mod, a high correlation was recently measured between the turbulence at the outer midplane seen with GPI and Langmuir probe measurements near the X-point region which mapped magnetically to the region viewed by the GPI, and similarly between the outer midplane region that mapped magnetically to Langmuir probes in the outer divertor target plates [19].…”
Section: Introductionmentioning
confidence: 98%
“…20. 114 The resulting flows can be measured and are found to be near the sound speed as the plasma expands into a near vacuum. 113 The effects of these flows on the H-mode threshold are discussed in Sec.…”
Section: Poloidally Asymmetric Transport and Sonic Sol Flowsmentioning
confidence: 99%
“…It is highly likely that cross-field drifts, shown to be experimentally important in the PFR [16,17,18] will be required to match the experimental trends in the PFR conditions. Drifts will also affect the heat transport into the PFR, which is assumed to be purely diffusive with the diffusivities scaled to match the upstream conditions.…”
Section: Figure 11 A) Divertor T E Calculated By Emc3-eirene Before mentioning
confidence: 99%